2018
DOI: 10.1136/bmj.k671
|View full text |Cite
|
Sign up to set email alerts
|

Plasma 25-hydroxyvitamin D concentration and subsequent risk of total and site specific cancers in Japanese population: large case-cohort study within Japan Public Health Center-based Prospective Study cohort

Abstract: ObjectiveTo evaluate the association between pre-diagnostic circulating vitamin D concentration and the subsequent risk of overall and site specific cancer in a large cohort study.DesignNested case-cohort study within the Japan Public Health Center-based Prospective Study cohort.SettingNine public health centre areas across Japan.Participants3301 incident cases of cancer and 4044 randomly selected subcohort participants.ExposurePlasma concentration of 25-hydroxyvitamin D measured by enzyme immunoassay. Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
70
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 55 publications
5
70
2
Order By: Relevance
“…Similar to the trend observed in other Asian countries, the prevalence of vitamin D insufficiency or deficiency was much higher in adolescent girls and young adult women than other age groups, even the elderly [5,7]. Epidemiologic studies have shown that vitamin D insufficiency or deficiency is closely associated with chronic diseases, such as tumors, cardiovascular diseases, and diabetes [8][9][10][11][12][13]. Indeed, vitamin D is fat soluble, meaning that it can be stored in body fat (BF) tissues, and excessive BF can reduce 25(OH)D levels in the body, especially in obese individuals.…”
Section: Introductionsupporting
confidence: 68%
“…Similar to the trend observed in other Asian countries, the prevalence of vitamin D insufficiency or deficiency was much higher in adolescent girls and young adult women than other age groups, even the elderly [5,7]. Epidemiologic studies have shown that vitamin D insufficiency or deficiency is closely associated with chronic diseases, such as tumors, cardiovascular diseases, and diabetes [8][9][10][11][12][13]. Indeed, vitamin D is fat soluble, meaning that it can be stored in body fat (BF) tissues, and excessive BF can reduce 25(OH)D levels in the body, especially in obese individuals.…”
Section: Introductionsupporting
confidence: 68%
“…(5) Observational epidemiological studies have found an inverse association of vitamin D status with risk of total cancer incidence and mortality. (6)(7)(8) However, a recent meta-analysis of randomized controlled trials (RCTs) has demonstrated a divergent effect of vitamin D supplementation, which reduces total cancer mortality but does not lower total cancer incidence in the general population, supporting a broad benefit of vitamin D in cancer prognosis. (9) Consistent with this hypothesis, observational cohort studies have shown improved survival in cancer patients with higher circulating vitamin D concentrations, measured before or shortly after diagnosis of cancer.…”
mentioning
confidence: 99%
“…Vitamin D is a hormone that regulates the calcium phosphate metabolism and its deficiency causes osteoporosis. At the same time low levels have been associated with an increased risk for melanoma and breast, colon, liver and lung neoplasms, among others . There is controversy over the optimum serum levels of 25(OH)D 3 .…”
Section: Introductionmentioning
confidence: 99%
“…At the same time low levels have been associated with an increased risk for melanoma and breast, colon, liver and lung neoplasms, among others. [3][4][5][6][7][8][9][10] There is controversy over the optimum serum levels of 25(OH)D 3 . 11,12 In general, it has been suggested that insufficiency, deficiency and sufficiency occur at 25(OH)D 3 levels of ≤ 20 ng/mL, 21-29 ng/mL and ≥ 30 ng/mL, respectively.…”
Section: Introductionmentioning
confidence: 99%